Digital Tip Amputations from the Perspective of the Nail - Lloyd Champagne; Joshua W. Hustedt; Robert Walker; John Wiebelhaus; N. Ake Nystrom (Advances in Orthopedics)
The management strategy proposed herein for fingertip amputations advocates secondary healing with preservation of appearance as well as function. Conservative healing is more likely to result in a sensate, nontender, and cosmetically acceptable fingertip compared to surgical management in many clinical scenarios. This manuscript examines in detail the extent of fingertip injury and defines the relationship of injury to final fingertip outcome. A classification is presented, which allows adequate initial counseling regarding prognosis, and predicts the need for secondary corrective surgery.